TINJAUAN KOMPREHENSIF TERHADAP SUMBER-SUMBER DALAM HUKUM PIDANA DAN ISU-ISU TERKAIT - Rachel Milafebina; Rasji i (Jurnal Ilmiah Wahana Pendidikan, 2023)
For Indonesians as well as other people around the world, terrorism is a very frightening crime. As mandated by the 1945 Constitution, the Republic of Indonesia is obliged to protect all Indonesian citizens and all Indonesian bloodshed. Consequently, the state is obliged to protect all its citizens from the threat of national or international terrorism. The purpose of writing is that the reader understands criminal issues related to systematic Indonesian governance. This article is based on normative legal research that utilizes secondary data in the form of primary and secondary legal documents. Utilization of criminal law to eradicate terrorism, as stated in Law Number 15 of 2003, among others, by making it illegal. Terrorism-related crime groups and related crimes are the focus of criminalization policies. It turns out that the law still faces challenges and deficiencies in its implementation so that it requires modification in the future.